2009
DOI: 10.1111/j.1540-8191.2009.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Methylprednisolone on Levels of Neuron-Specific Enolase in Cardiac Surgery: A Corticosteroid Derivative to Decrease Possible Neuronal Damage

Abstract: The lower levels of NSE in patients who received methylprednisolone may suggest that corticosteroids might be useful in decreasing possible neuronal damage during heart surgery. However, we were not able to demonstrate an adverse neurological outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 47 publications
0
25
0
3
Order By: Relevance
“…The authors found that high serum level of S100 β protein is associated with increased levels of serum inflammatory mediators and systemic inflammatory response during CPB [15]. Additionally, Demir et al analysed thirty patients' serum neuron-specific enolase (NSE), interleukin-6 (IL-6), and IL-10 before CPB and 4 and 24 hours after the end of extracorporeal circulation and found that serum cytokine and NSE levels were significantly associated with neuronal damage [16]. …”
Section: Predictors Of Brain Injury With On-pump Cardiac Surgerymentioning
confidence: 99%
“…The authors found that high serum level of S100 β protein is associated with increased levels of serum inflammatory mediators and systemic inflammatory response during CPB [15]. Additionally, Demir et al analysed thirty patients' serum neuron-specific enolase (NSE), interleukin-6 (IL-6), and IL-10 before CPB and 4 and 24 hours after the end of extracorporeal circulation and found that serum cytokine and NSE levels were significantly associated with neuronal damage [16]. …”
Section: Predictors Of Brain Injury With On-pump Cardiac Surgerymentioning
confidence: 99%
“…Fakat ameliyat öncesi dönemde uygulanan 1 g metilprednizolon, KABG uygulanan hastalarda ameliyat sonrası dönemde 24 saatte NSE'yi anlamlı şekilde azaltmaktadır. [45] Bununla birlikte, araştırmacılar NSE düzeylerindeki artış ile KPB süresi arasında ilişki bulamamıştır. [45] Bayram ve ark.…”
Section: Nöron Spesifik Enolazunclassified
“…[45] Bununla birlikte, araştırmacılar NSE düzeylerindeki artış ile KPB süresi arasında ilişki bulamamıştır. [45] Bayram ve ark. [46] ameliyat sonrası S100b proteini düzeyinin atan kalpte KABG'de, KPB ile CABG'ye oranla (pulsatil ya da non-pulsatil akım uygulanan) daha düşük olduğu ve perfüzyon türünden etkilenmediğini bildirmişlerdir.…”
Section: Nöron Spesifik Enolazunclassified
See 1 more Smart Citation
“…On the other hand, systemic inflammation can be suppressed pharmacologically and there are hints that application of corticosteroids might be of advantage during CPB in lowering NSE (neuron specific enolase, also a marker for cerebral injury) and S100β protein release, although this is still a matter of debate [20]. Whether suppression of inflammation also has a protective effect on the neurological outcome has yet to be proven.…”
Section: Introductionmentioning
confidence: 99%